2010
DOI: 10.1373/clinchem.2009.141341
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Assessment of Elderly Patients with Symptoms of Heart Failure by Combining High-Sensitivity Troponin T and N-Terminal Pro–B-Type Natriuretic Peptide Measurements

Abstract: BACKGROUND N-terminal pro–B-type natriuretic peptide (NT-proBNP) is a useful biomarker in heart failure assessment, whereas measurement of cardiac troponin is central in the diagnosis of patients with acute coronary syndromes. This report examined the prognostic use of combining high-sensitivity cardiac troponin T (hs-cTnT) and NT-proBNP measurements in elderly patients presenting to a primary care center with symptoms associated with heart failure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 34 publications
4
16
0
Order By: Relevance
“…Earlier studies with second and third generation assays for cTn showed that both biomarkers are independently related with future cardiac events [47], with an additive prognostic value [12,48,49]. Similar conclusions were reached also in studies evaluating NP and hsTn [16,50,51]. This is consistent with the fact that Tn and NPs are related to different pathophysiological mechanisms: myocardial stretch and myocardial damage, respectively.…”
Section: Discussionsupporting
confidence: 79%
“…Earlier studies with second and third generation assays for cTn showed that both biomarkers are independently related with future cardiac events [47], with an additive prognostic value [12,48,49]. Similar conclusions were reached also in studies evaluating NP and hsTn [16,50,51]. This is consistent with the fact that Tn and NPs are related to different pathophysiological mechanisms: myocardial stretch and myocardial damage, respectively.…”
Section: Discussionsupporting
confidence: 79%
“…The reduction of platelet aggregation at 0 h and 2 h after PCI relative to pre PCI value in both DM and non-DM groups. Data are shown as mean ± SEM; DM -diabetes mellitus; *p < 0.05. other non-ischemic factors such as heart failure, diabetes mellitus and ventricular hypertrophy [14,24]. Correlation analysis was done between hs-cTnT 2h after PCI and baseline characteristics of patients, and it was found that hs-cTnT 2h after PCI was strongly associated only with baseline hs-cTnT level, but not with other factors, suggesting that hs-cTnT levels at 2 h after PCI in our patients is not significantly affected by other factors.…”
Section: Discussionmentioning
confidence: 57%
“…8,9,21,22 In the 2 largest samples studied to date, hs-cTnT was indeed detectable (Ն3 ng/L) in 86% of the patients in Val-HeFT and 98% of those from GISSI-HF. However, the exact mechanisms for troponin release from cardiac myocytes and its clearance from the circulation remain speculative, especially in chronic HF.…”
Section: Masson Et Al Serial Troponin and Outcome In Chronic Hf 283mentioning
confidence: 91%